Simple Routine Tests to check animal feed quality - Das, Lalatendu Keshary; Mishra, Prasanta Kumar (Indian Farming, 2017)
Small and marginal dairy farmers are the backbone of Indian dairy sector as they contribute significantly to the milk production of our country. To check fraudulent practices in animal feed industry, BIS (Bureau of Indian Standard) has come up certain standards with respect to quality of raw feed ingredients as well as whole feed formulations. But due to ignorance and lack of consciousness, these standards are often not put into practices by dairy farmers. This eventually increases the risks of feed adulteration in different stages of feed processing until feed reaches to the farmers. So it is always advisable to prepare the animal feeds at the farm itself for feeding to the animals.